Econospingnning : - Epstein, Gene (John Wiley & Son, 2006)
ene Epstein knows a thing or two about economic data. Before becoming the Economics Editor for Barron's in 1993, he was a senior economist at the New York Stock Exchange. Now in Econospinning, Epstein supplies readers with a book that attempts to cut through the veil of economic misinformation commonly reported in today's media.